2020
DOI: 10.20944/preprints202008.0623.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<em>Leptospermum scoparium</em> (Mānuka) and <em>Cryptomeria japonica</em> (Sugi) Leaf Essential Oil Seasonal Chemical Variation and Their Effect on Antimicrobial Activity

Abstract: This study evaluated the antimicrobial activity of Leptospermum scoparium (Mānuka) and Cryptomeria japonica (Sugi) essential oils and assessed the effect of seasonal chemical variation on the oils&rsquo; antimicrobial efficacies. Plate based assays were conducted to elucidate the oils&rsquo; spectrum of in vitro antimicrobial activity and to determine the oils&rsquo; minimum inhibitory concentrations (MIC) as a measure of antimicrobial efficacy. Gas chromatography &ndash; mass spectrometry was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Such variation can be attributed to several factors, including exogenous (such as light, precipitation, growing region, nature of the soil and season) or/and endogenous factors (e.g., plant age, plant organ, developmental stage and genotype). Also, the EO yield can be influenced by these same parameters [27,[46][47][48] along with the extraction method used. However, there are conflicting reports in the literature about the influence of environmental conditions on C. japonica EO chemotypes, with some studies reporting no effects [33] and others [27] indicating that environmental factors strongly influenced the EO chemical profile.…”
Section: Yield and Chemical Composition Of C Japonica Eomentioning
confidence: 99%
“…Such variation can be attributed to several factors, including exogenous (such as light, precipitation, growing region, nature of the soil and season) or/and endogenous factors (e.g., plant age, plant organ, developmental stage and genotype). Also, the EO yield can be influenced by these same parameters [27,[46][47][48] along with the extraction method used. However, there are conflicting reports in the literature about the influence of environmental conditions on C. japonica EO chemotypes, with some studies reporting no effects [33] and others [27] indicating that environmental factors strongly influenced the EO chemical profile.…”
Section: Yield and Chemical Composition Of C Japonica Eomentioning
confidence: 99%
“…Terpene content is affected by SCs (Merk et al, 1988). For example, in Japanese cedar (Cryptomeria japonica) (Bang et al, 2020), the maximum content of terpenes was observed in summer. Among most other conifers, such as white spruce (Pinus glauca) (von Rudloff, 1972), blue spruce (Pinus pungens) (von Rudloff, 1975), and Picea abies (Schnwitz et al, 1990;Kamaityt-Bukelskien et al, 2021), there is a similar seasonal pattern of variation in the number of terpenes.…”
Section: Introductionmentioning
confidence: 99%